3D presentation of a neurotrophic factor for the regulation of neural progenitor cells. (August 2014) - Zhou, Kun; Thouas, George; Bernard, Claude; Forsythe, John S
Background: Adequate cell–scaffold interactions and neurotrophin support are essential factors for neural regeneration.Aim: To provide insight into the biofunctionalization of complex 3D scaffolds with nanoscale precision, as well as the effect of spatial distribution of brain-derived neurotrophic factor (BDNF) and its prolonged stimulation in combination with enhanced cell affinity of nanofibrous scaffolds on the survival/proliferation and neurite outgrowth.Methods & materials: We developed a versatile approach using layer-by-layer self-assembly to incorporate cell adhesion and spatial representation of neurotrophic factors into complex nanofibrous scaffolds.Results: Heparin/poly-L -lysine (PLL) polyelectrolyte multilayers (PEMs) were deposited on electrospun poly-ε-caprolatone nanofibers. Well-controlled amounts of BDNF were immobilized on the PEM-modified nanofibers. In addition, longer neurite outgrowth was observed in neural progenitor cells cultured on PLL-terminating PEM scaffolds. The immobilized BDNF on PLL-terminated PEM scaffolds resulted in significantly longer neurites and higher cell numbers (p < 0.01) compared with BDNF-free and BDNF-adsorbed PLL-terminating scaffolds. Interestingly, there was no upregulation of TrkB-FL, TrkB-T1 or GAP-43 mRNAs with immobilized BDNF in day 5 cultures. Discussion &conclusion: This work reinforces the importance of the combinatorial effects of biomaterial scaffold nanostructure and spatial presentation of neurotrophins in directing neural progenitor cell fates. Original submitted 18 January 2013; Revised submitted 3 May 2013